A Bottleneck Effect in Perfluoropropene. Issue 4 (1994) - Torresano, J. A.; Santos, M.; González-Díaz, P. F.
Abstract : By investigating the infrared dissociation yield of perfluoropropene under a convenient range of experimental conditions on pressure, laser fluence and number of irradiation shots, we have seen that i) besides the already known final products, C2 F4 and C2 F6, the dissociation of this molecule also produces polytetrafluoroethylene, and ii) contrary to what one should expect from its rather large molecular size, perfluoropropene opposes a strong bottleneck effect against absorption of resonant infrared radiation, at least for irradiation fluences smaller than ≈ 1.8 Jcm -2